Condition monitoring and fault diagnosis of fluid power system - Yu, Li. (2008)
This report is concerned with the condition monitoring and fault diagnosis of fluid power components. The hydraulic systems involved were an oil hydraulic system and a water hydraulic system. The oil/water hydraulic system consisted of power pack, directional control valves, hydraulic motor and hydraulic cylinder. The method employed for condition monitoring was vibration measurements. Amplitude spectrum analyses were used to analyze the running condition of the hydraulic cylinder and motor. The experiments included developing the procedures for fault detection on leakage through seal and piston cracks. LabVEEW, a graphical programming language, was used to form an effective analysis of the amplitude and power spectra. It integrates data acquisition, analysis and presentation into one system.